Advanced use of learning technologies in higher education: AduLeT project big picture - Gonçalves, Vitor (2017)
AduLeT aims at creating a Community of Practice (CoP) to improve the teaching quality of lecturers by enhancing their skills concerning the use of technologies in an advanced way. The main idea is training the teacher on how a specific teaching method can be combined with a certain technology in addition to providing guidelines, best practice and strategy concepts for lecturers and universities. The CoP should also supply the means to ensure contact with other lecturers and therefore share experiences within teaching using Technology Enhanced Learning (TEL). The consortium of this project consists of the following partners: - Ludwigsburg University of Education (Germany) - Complutense University of Madrid (Spain) - Humak University of Applied Sciences (Finland) - University Pallasz Athéné (Hungary) - International Education and Training Institution, Pixel (Italy) - Open University of the Netherlands (Netherlands) - Polytechnic Institute of Bragança (Portugal).